Implementasi Konsep Islam Ramah Lingkungan - Rahma Hazalia; Indah Muliati (An-Nuha, 2022)
This study aims to examine the implementation of the concept of environmentally friendly Islam at MTsN 2 Padang Pariaman. This study uses a qualitative method with a descriptive approach. The data used in this study were taken through direct interviews with seven madrasah residents consisting of the principal, administrative staff, two teachers, and three students. This study was conducted to describe (1) the concept of environmentally friendly Islam in schools. (2) Implementation of environmentally friendly Islamic concepts in schools. (3) Inhibiting and supporting factors in the implementation of environmentally friendly Islamic concepts in schools. After the data was obtained and then analyzed, it was found that the concept of environmentally friendly Islam at MTsN 2 Padang Pariaman there were four concepts applied, namely maintaining cleanliness, reforestation, preserving natural resources, and maintaining human health. The implementation of the environmentally friendly Islamic concept in this school has begun to be implemented well. Such as being prohibited from littering, making compost, planting ornamental or medicinal plants, and having routine controls from the Puskesmas to students.